(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India’s banking sector is a study in disparity it ropes the world’s quickest developing substantial economy yet is grappling about challenges that test its quality and strength. Banking system creates possibilities in the development of economy. The banking sector is the life saver of any modern economy. It is one of the vital mainstays of financial system, which assumes an essential part in the success or failure of an economy.